Views of Teachers, Intern doctors and Students regarding Feedback on Formative Assessment during MBBS Course in Bangladesh (Bangladesh Journal of Medical Education, 2017)
Objective(s): To explore the present status of feedback following formative assessment during MBBS course in Bangladesh.Methodology: This study was conducted in eight (4 govt. and 4 non govt.) medical colleges in Dhaka and outside Dhaka. The study period was July 2014 to May 2015. Total 50 teachers, 150 intern doctors, 250 students participated in this study. Different structured, self-administered questionnaire were used to collect data from the teachers, intern doctors and students.Result: Majority of the teachers (58%) , intern doctors (89%) and students (87%) disagreed about return of written answers script to the students after formative assessment, while few teachers (12.5%) teachers used to return those , out of their own interest. In this study, 80% teachers, 60% intern doctors and 50% students mentioned that individual feedback was not practiced on SOE/Oral examinations after formative feedback. Most (62.3%) of the intern doctors and students (63%) opined that the feedback they received after formative assessment were not uniform from all departments. Majority (56%) of the teachers pointed that, the timing of providing feedback was uncertain and 48% teachers declared that they gave feedback after formative assessment by marks/grade in groups whereas only 6% teachers provided it personally. Teachers (76%) added that through formative assessments followed by feedback they could identify the learning gaps and weaknesses of the students. According to teachers (86%), intern doctors (74.5%) and students (59.2%), it helped to reduce the fear in subsequent assessment. All of the respondents (teachers, intern doctors and students) figured out the factors responsible for inadequate feedback after formative assessment as compact class schedule (58%, 44.8%, 56.5% respectively), frequent assessment (48%, 49.7%, 48.1% respectively) and inadequate number of stuff (44%, 31.2%, 37.7% respectively). Teachers, intern doctors and students suggested that training of the teachers on feedback process, appointing more teachers, limiting the number of classes and formative assessments, ensuring the feedback after each formative assessments may improve the present situation of feedback in MBBS course.Conclusion: In our country context feedback following formative assessment during MBBS course are not being given following any standard manner. In this study it was figured out that different types of formative assessment are important at different phases of MBBS course. On the basis of respondents' (Teachers, Intern doctors and students) opinion, it can also be concluded that feedback is not being provided in time after formative assessment. Individual feedback is not also being practiced on SOE and practical/clinical examinations after formative assessment, rather it is being provided by some teachers' own interest but not uniformly by all the departments.Bangladesh Journal of Medical Education Vol.7(2) 2016: 2-8